Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

is the expression 5 (3m+2p) -4m equivalent to the expression 13p+11m-3p?

Sagot :

 5 (3m+2p) -4m= 15m +10p -4m
=11m +10p
--------------------------------------------------------
13p+11m-3p=10p -11m
-----------------------------------------------------------
Yes, 5 (3m+2p) -4m is  equivalent to the expression 13p+11m-3p as i worked out for you.. Hope this helps you!!! =')

xokkxo
5(3m +2p) - 4m = 13p + 11m - 3p
15m + 2p - 4m = 10p + 11m
11m + 2p = 10p + 11m
2p = 10p
No. The equations don’t have an answer